Tanggapan Konsumen tentang Manfaat Virgin Coconut Oil (VCO) untuk Kesehatan (Studi Kasus) - Irwan Hanafi (Pendidikan Biologi FKIP UMMY, 2022)
In its utilization, VCO can be consumed directly or used for cooking with many benefits for health, preventing and curing various diseases. The research entitled